Role of Possum Scoring System to Assess the Expected Morbidity and Mortality in Patients Undergoing Laparotomy - Manoharan, G.V.; Vijayalakshmi, G. (Medical Science: Trends and Innovations Vol. 1, 2025)
Background: In the era of evidence-based medicine, a sound knowledge of expected complications is essential in surgical practice. Understanding and stratifying patients based on an objective scoring method is imperative in both patient education and surgical team preparedness. Among the variety of scoring systems used to identify the “high-risk” patient, POSSUM scoring is the most widely used. Methods: This was a descriptive study done on 154 patients who underwent midline laparotomy in this institute from October 2016 to October 2017. Patients undergoing laparotomy were sampled by using purposive sampling and their physiological severity score on admission and operative severity score at the end of 30 days were calculated. The morbidity and mortality rates were compared with the POSSUM score predicted rates. Results: In the elective surgery group morbidity rates were higher in patients with higher POSSUM scores but due to low overall morbidity conclusions could not be drawn. while in the emergency group, POSSUM-predicted morbidity correlated well with observed results. The low mortality rates in the entire study population precluded meaningful analysis. Conclusion: POSSUM has been proven to be one of the best scoring systems that could predict morbidity and mortality risk with reasonable accuracy. POSSUM scoring system has an undeniable advantage in our set-up for better patient counseling, improving the surgical outcomes in both emergency and elective wards and better management of limited resources and manpower.